The Guidebook and the Medicine Pole: Staging Memory at a Nineteenth Century Battle Site in the American West - Wendy Harding; Jacky Martin (Les Cahiers de Framespa)
Visitors to the Lava Beds National Monument discover a site where the National Park Service has to orchestrate features of geological, historical, and environmental interest. This article examines the way in which it presents one of these features, «Captain Jack’s Stronghold», the site of a confrontation between the U.S. army and a small band of Modoc Indians that took place in 1872-73. In following the self-guided tour, visitors engage in a quasi-theatrical performance that encourages them to «emplace» themselves in the present through a commemorative act that reconstructs the past in order to conciliate conflicts in the contemporary community and to define the nation in the present. This article reflects on the power of landscape to create a sense of history and to foster a sense of place. The former battleground is the site of an inevitably disputed process of collective emplacement.